Fakta empiris kurva U-terbalik Kuznets mengenai pertumbuhan ekonomi di Provinsi Jambi - Alin, Nessy Fameylan; Heriberta, Heriberta; Umiyati, Etik (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
The study aimed to analyze the development of the gini ratio and income per capita and to prove whether the hypothesis of Kuznets (U-inverted curve) applies in Jambi Province. To prove whether the Kuznets hypothesis applies in Jambi Province through an analysis of the relationship between per capita income and the gini ratio. The results of the study found that the growth of per capita income in Jambi Province was followed by the development of relatively fluctuating income inequality. Therefore, the Kuznets' hypothesis is not valid in Jambi Province.